Plane Symmetric Space Time with Mesonic Cosmic Strings in Bimetric Relativity - Deo, S. D.; Qureshi, A. A. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, plane symmetric space-time is studied with cosmic strings coupled with massive scalar field in the context of Rosen™s Bimetric Theory of Relativity. Here it is shown that only vacuum model can be constructed.